Analysing, Planning and Valuing Private Firms New Approaches to Corporate Finance - Beltrame, Federico; Sclip, Alex. (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2023)
"In this book, the authors were able to think outside the box, providing methodologies and approaches that can actually be used for the practice of unlisted company analysis and valuation, while maintaining scientific rigor. Unlike other books on the valuation of privately held companies, the methodologies can be used without resorting to sophisticated tools or proprietary information, highlighting their extreme applicability. Highly recommended." --Enrico Maria Cervellati, Associate Professor of Corporate Finance, Link Campus University, Rome Corporate finance plays a vital role in every business as it pertains to an array of financing and investment decisions. Where most corporate finance books provide tools for public companies, this book presents new approaches and methods for planning and valuing private firms. Chapters discuss how typical valuation methods may not be perfectly adaptable to private firms and their investment decisions: in particular showing how the widely used Capital Asset Pricing Model cannot be precisely applied for the estimation of cost of equity for private companies, and the limitations of market multiples which may not match individual company features. The book suggests new ways of financial forecasting that can be better tailored to private businesses, such as by exploiting the concept of financial breakeven based on debt serviceability that departs from the more traditionally used concept of the revenue-cost breakeven. Topics including financial planning, working capital management, the cost of capital, and valuation methods are all covered. This book will be of interest to consultants, analysts and accountants working in private firms, as well as academics and students who are interested in an empirical assessment of the role of corporate finance in private businesses versus larger public companies. Federico Beltrame is Associate Professor in Corporate Finance in the Department of Economics and Statistics, University of Udine, where he teaches corporate finance. Alex Sclip is Assistant Professor of Corporate Finance in the department of business administration of the University of Verona, where he teaches corporate finance at the undergraduate level and strategic finance at the graduate level. .
Chapter 1: Corporate Financial Analysis -- Chapter 2: The financial and economic forecast -- Chapter 3: The cost of capital for private businesses -- Chapter 4: Business valuation through market multiples -- Chapter 5: Conclusions - Putting all together for valuing a start - up.
Keywords: Business enterprises -- Finance; Consolidation and merger of corporations; Accounting; Financial statements; Corporate Finance; Mergers and Acquisitions; Financial Accounting; Financial Reporting